Improving yield potential in crops under elevated CO2: Integrating the photosynthetic and nitrogen utilization efficiencies - Kant, Surya; Seneweera, Saman; Rodin, Joakim; Materne, Michael; Burch, David; Rothstein, Steven J.; Spangenberg, German (Frontiers in Plant Science, 2012)
Increasing crop productivity to meet burgeoning human food demand is challenging under changing environmental conditions. Since industrial revolution atmospheric CO2 levels have linearly increased. Developing crop varieties with increased utilisation of CO2 for photosynthesis is an urgent requirement to cope with the irreversible rise of atmospheric CO2 and achieve higher food production. The primary effects of elevated CO2 levels in most crop plants, particularly C3 plants include increased biomass accumulation, although initial stimulation of net photosynthesis rate is only temporal and plants fail to sustain the maximal stimulation, a phenomenon known as photosynthesis acclimation. Despite this acclimation, grain yield is known to marginally increase under elevated CO2. The yield potential of C3 crops is limited by their capacity to exploit sufficient carbon. The “C fertilization” through elevated CO2 levels could potentially be used for substantial yield increase. Rubisco is the rate-limiting enzyme in photosynthesis and its activity is largely affected by atmospheric CO2 and nitrogen availability. In addition, maintenance of the C/N ratio is pivotal for various growth and development processes in plants governing yield and seed quality. For maximising the benefits of elevated CO2, raising plant nitrogen pools will be necessary as part of maintaining an optimal C/N balance. In this review, we discuss potential causes for the stagnation in yield increases under elevated CO2 levels and explore possibilities to overcome this limitation by improved photosynthetic capacity and enhanced nitrogen use efficiency. Opportunities of engineering nitrogen uptake, assimilatory, and responsive genes are also discussed that could ensure optimal nitrogen allocation towards expanding source and sink tissues. This might avert photosynthetic acclimation partially or completely and drive for improved crop production under elevated CO2 levels.